2018
DOI: 10.1038/s41409-017-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib: a steroid sparing agent in chronic graft-versus-host disease

Abstract: Inhibition of the Janus-associated kinases (JAK) with ruxolitinib (RUX) reduces graft-versus-host disease (GVHD) in preclinical and clinical models. In total 19 allograft recipients with moderate/severe steroid-dependent chronic GVHD received RUX as ≥2nd line salvage. RUX was well tolerated, and led to complete/partial resolution of oral (92/7%), cutaneous (82/0%), hepatic (71/28%), gastro-intestinal (75/17%), musculoskeletal (33/67%), pulmonary (0/80%), scleroderma (0/75%), vaginal (0/75%), and ocular (0/100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 13 publications
(13 reference statements)
5
53
1
4
Order By: Relevance
“…Zeiser et al reported a response rate of 81.5% in patients with steroid‐refractory acute GvHD and 85.4% in patients with chronic GvHD . Khoury et al observed high responses in steroid‐refractory chronic GvHD . Finally, based on the results of REACH1 clinical trial, in which our institution have participated, FDA approved ruxolitinib as the first and only FDA‐approved treatment for steroid‐refractory acute GvHD after alloHCT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Zeiser et al reported a response rate of 81.5% in patients with steroid‐refractory acute GvHD and 85.4% in patients with chronic GvHD . Khoury et al observed high responses in steroid‐refractory chronic GvHD . Finally, based on the results of REACH1 clinical trial, in which our institution have participated, FDA approved ruxolitinib as the first and only FDA‐approved treatment for steroid‐refractory acute GvHD after alloHCT.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, inhibition of JAK1/2 via ruxolitinib has been explored as a possible treatment for GvHD after alloHCT, based on ruxolitinib's potent GvHD‐sparing effects seen in mouse models . In humans, there have been several reports using ruxolitinib in GvHD following alloHCT . Zeiser et al reported a response rate of 81.5% in patients with steroid‐refractory acute GvHD and 85.4% in patients with chronic GvHD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in a moderate/severe cGVHD, ruxolitinib induces high response rates, and reduction to physiologic doses/discontinuation of prednisone was possible in 90% of patients at a median of 106 days (range, 31-365) from starting ruxolitinib [4,5]. In conclusion, ruxolitinib appears to be a viable treatment option for SR-aGVHD.…”
Section: Dear Editorsmentioning
confidence: 87%
“…Our study did not have explicit eligibility criterion and may reflect more real-world use of ruxolitinib for SR-aGVHD. Several patients were given very short durations of ruxolitinib < 14 days before transitioning to comfort care or expiring, and these patients were excluded as response was difficult to assess and likely does not reflect the efficacy of ruxolitinib.Additionally, in a moderate/severe cGVHD, ruxolitinib induces high response rates, and reduction to physiologic doses/discontinuation of prednisone was possible in 90% of patients at a median of 106 days (range, 31-365) from starting ruxolitinib [4,5]. In conclusion, ruxolitinib appears to be a viable treatment option for SR-aGVHD.ª 2019 Steunstichting ESOT…”
mentioning
confidence: 94%